The Role of Income and Substitution in Commodity Demand - Baffes, John (World Bank E-Library Archive, 2020)
This paper presents estimates of time-varying income elasticities of demand for energy and metal commodities. The analysis finds that the elasticities are close to unity, evaluated at world median per capita income levels. Furthermore, the estimates confirm that as income rises, demand growth for industrial commodities slows and eventually plateaus. Indeed, estimates for aggregate metals and energy differ by an order of magnitude throughout the income spectrum: from a low of 0.2 for advanced economies to nearly 2 for low-income countries. The analysis, which accounts for substitutability by estimating group aggregates as well as individual commodities with cross-price effects, is based on a panel autoregressive distributed lag model covering 1965-2018, for up to 63 countries